Réponses

Meilleure réponse !
2014-05-17T22:36:03+02:00
E = 2x+1 + (2+x)-(x-2)
E = 2x+1 +2+x-x+2
E = 2x+x-x +1+2+2
E = 2x+5

F = 2(3-x) - (x-7)4
F = 2*3 +2*(-x) - (x*4 + (-7)*4) (* signifie multiplié par)
F = 6 -2x- (4x-28)
F = 6 -2x-4x+28
F = -6x + 34

G = x(-2x²+1) +x^3 (^ se lit puissance)
G = -2x²*x +1*x + x^3
G = -2x^3 + x + x^3
G = -x^3 + x

H = (1-x)(3x-2)
H = 1*3x + 1*(-2) + (-x)*3x + (-x)*(-2)
H = 3x -2 -3x² +2x
H = -3x² + 5x - 2

2014-05-17T23:16:13+02:00
La g est un peu plus difficile donc: g = x(-2x^2+1) +x^3 g = -2x^2 +1*x + x^3 g = -2x^3 + x + x^3 g = -x^3 + x